O Desenvolvimento sem Norte nem Sul - Fernando Jorge Cardoso (Cadernos de Estudos Africanos)
Development entered the lexicon of Social Sciences in the forties of last century, in the framework of non-industrialised economies, without relevant flows of private domestic capital, with most of the population living from agriculture and strongly dependent upon the exportation of commodities. As social, technological, environmental and knowledge change occurred, the concept extended to other fields, from economics to culture, from ecology to management. Today, with the deepening of globalisation and the blurring of the barriers to trade and capital, the concept became universal and no more applied only in the framework of underdeveloped economies. This way, the debate about development, after the end of the East-West analytical paradigms, challenges the current North-South analysis.